Challenges and opportunities of using egg parasitoids in FAW augmentative biological control in Brazil - Bueno, Adeney de F.; Sutil, Weidson P.; Maciel, Rodrigo M.A.; Roswadoski, Leonardo; Colmenarez, Yelitza C. [UNESP]; Colombo, Fernanda C. (Elsevier, 2023)
The fall armyworm (FAW) (Spodoptera frugiperda) is a transboundary insect pest with high potential for rapid dispersal due to its natural ability to spread, its polyphagous habit and a remarkable ability to develop resistance to insecticides. As a side effect, this adaptability can cause unprecedented impacts to agriculture, especially to maize (Zea mays) if not managed properly. Currently, the control of this pest is carried out predominantly with synthetic insecticides although the use of biological control agents constitutes an important, sustainable and efficient tool within integrated pest management (IPM). Among the different natural enemies reported for FAW, the egg parasitoids Telenomus remus and Trichogramma spp. are the most studied and used species, both showing great potential for augmentative biological control (ABC) of FAW and other armyworms that often attack maize. In this context, this article reviews the difficulties and opportunities of the use of Telenomus remus and Trichogramma spp. to control FAW. A new strategy of performing releases of combined parasitoid species is introduced. Furthermore, the benefits of releasing fed adults inside capsules instead of pupae close to emergence are discussed. A selection of published results is presented and discussed with respect to a more sustainable FAW management.
Keywords: Integrated pest management; Spodoptera frugiperda; Telenomus remus; Trichogramma spp.